Holocene dynamics of tree taxa populations in Italy - Magri, Donatella; Agrillo, Emiliano; Di Rita, Federico; Furlanetto, Giulia; Pini, Roberta; Ravazzi, Cesare; Spada, Francesco (Review of Palaeobotany and Palynology, 2014)
The Holocene distribution of nine tree taxa (Picea, Abies, Betula, Fagus, Carpinus betulus, Corylus, deciduous and evergreen Quercus, and Olea) in Italy is visually shown by pollen maps. A hundred pollen sites were selected, percentageswere derived fromthe original pollen counts or digitized frompublished diagrams, and represented on maps in subsequent time windows at 1000-year intervals. The pollen maps depict the Holocene history of Italian forest cover as a complex puzzle influenced by very diverse climate, physiography, edaphic and ecological processes, and a long history of human activity. A reasonably goodmatch between the abundance and distribution of pollen data during the last thousand years and the current tree species distribution in Italy indicates that the Holocene pollen maps may represent a fundamental basis for a better understanding of the modern vegetation patterns, often showing discontinuous ranges and complex distributions. Although clear latitudinal gradientswere not detected, regions characterized by high precipitation values hosted dense forest cover since the Holocene onset, while areas with arid climate experienced a delayed increase in trees and a faster decrease during the last four millennia. Fagus, C. betulus and Picea showdisplacement in their distribution inItaly in the course of theHolocene.Other taxa, likedeciduous and evergreen Quercus, and Betula have always occupied the same locations during the Holocene, but show changes in abundance. Abies had a broken distribution in Italy throughout the postglacial. Its populations are currently found within the regions they occupied at the onset of the Holocene. The importance of considering all the available records in their geographical context to reconstruct complex vegetational patterns is discussed.
Keywords: Database; Holocene; Italy; Pollen map; Woody taxon

Rapid climatic changes and resilient vegetation during the Lateglacial and Holocene in a continental region of south-western Europe - Aranbarri, Josu; González-Sampériz, Penélope; Valero-Garcés, Blas; Moreno, Ana; Gil-Romera, Graciela; Sevilla-Callejo, Miguel; García-Prieto, Eduardo; Di Rita, Federico; Mata, M. Pilar; Morellón, Mario; Magri, Donatella; Rodríguez-Lázaro, Julio; et al. (Global and Planetary Change, 2014)
Palynological, sedimentological and geochemical analyses performed on the Villarquemado paleolake sequence (987m a.s.l, 40°30′N; 1°18′W) reveal the vegetation dynamics and climate variability in continental Iberia over the last 13,500calyrBP. The Lateglacial and early Holocene periods are characterized by arid conditions with a stable landscape dominated by pinewoods and steppe until ca. 7780calyrBP, despite sedimentological evidence for large paleohydrological fluctuations in the paleolake. The most humid phase occurred between ca. 7780 and 5000calyrBP and was characterized by the maximum spread of mesophytes (e.g., Betula, Corylus, Quercus faginea type), the expansion of a mixed Mediterranean oak woodland with evergreen Quercus as dominant forest communities and more frequent higher lake level periods. The return of a dense pinewood synchronous with the depletion of mesophytes characterizes the mid-late Holocene transition (ca. 5000calyrBP) most likely as a consequence of an increasing aridity that coincides with the reappearance of a shallow, carbonate wetland environment. The paleohydrological and vegetation evolution shows similarities with other continental Mediterranean areas of Iberia and demonstrates a marked resilience of terrestrial vegetation and gradual responses to millennial-scale climate fluctuations. Human impact is negligible until the Ibero-Roman period (ca. 2500calyrBP) when a major deforestation occurred in the nearby pine forest. The last 1500years are characterized by increasing landscape management, mainly associated with grazing practices shaping the current landscape.
Keywords: aridity; Continental Iberia; Holocene; Multiproxy reconstructio; Pinewoods; Vegetation resilience

The cultural landscape near the ancient city of Tharros (central West Sardinia): vegetation changes and human impact - Di Rita, Federico; Melis, Rita Teresa (Journal of Archaeological Science, 2013)
The evolution of the cultural landscape in coastal western Sardinia is investigated by means of pollen analysis in the Mistras Lagoon sediments, near the ancient city of Tharros, with particular attention to changes in evergreen vegetation and the impact of human activity. The pollen diagram, spanning the time interval from 5300 to 1600 cal BP, documents the influence of man, climate, and geomorphic dynamics and on the evolution of a semi-open evergreen vegetation landscape and variations in extent of a salt-marsh environment. Anthropogenic indicators and microcharcoals concur in depicting increased land use coinciding with the Nuragic, Phoenician, Punic and Roman dominations. Pollen data, along with archaeobotanical evidence, suggest a prevailing arable farming economy, vocated to Vitis and cereals expoitation, during the Nuragic phase until 2400 cal BP, replaced since then by a prevailing stock rearing economy. Between 2050 and 1600 cal BP, a less intensive human impact on the landscape is profiled, consistently with the archaeologically documented abandonment of the rural villages in favour of a slow urbanization, experienced by the Sinis territory in Imperial times. The pollen record provides new insights into the history of important economic plants in the Mediterranean, such as Vitis, Olea and Quercus suber. The results of the pollen analysis reveal how the records of these taxa are primarily influenced by the cultural development of the Sinis region and secondarily by dynamics involving the natural companion vegetation.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: evergreen vegetation; Holocene; human impact; pollen; Sardinia

A Lateglacial and early Holocene pollen record from Valle di Castiglione (Rome): Vegetation dynamics and climate implications - Di Rita, Federico; Anzidei, Anna Paola; Magri, Donatella (Quaternary International, 2013)
A new pollen record from Valle di Castiglione near Rome (core VdC09) has been studied with the aim of providing a detailed reconstruction of the vegetation history of the Roman landscape between 13,800 and 7700 cal BP, in response to the Lateglacial and early Holocene climate events. An open landscape dominated by steppe vegetation characterized the Lateglacial, so that only a modest increase of trees took place during the Allerød interstadial. The Intra Allerød Cold Period induced instability in the development of the woody communities. The Holocene forest recovery started around 11,600 cal BP, but definite forest development occurred only around 11,100 cal BP, at the end of the Preboreal Oscillation, which produced an important re-expansion of herbs. The evergreen Mediterranean vegetation was constantly present in the landscape, even during the Lateglacial cold fluctuations. A clear early Holocene increase in evergreen trees corresponds to the attainment of high and stable values in the GISP2 δ18O curve, around 10,200 cal BP.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd and INQUA
Keywords: climate changes; deciduous and evergreen forests; Holocene; landscape (voyant); Mediterranean Region; Pollen analysis; Vegetation dynamics

Impacts of changing climate and land use on vegetation dynamics in a Mediterranean ecosystem: insights from paleoecology and dynamic modeling - Henne, Paul D.; Elkin, Ché; Colombaroli, Daniele; Samartin, Stéphanie; Bugmann, Harald; Heiri, Oliver; Tinner, Willy (Landscape Ecology, 2012)
Forests near the Mediterranean coast have been shaped by millennia of human disturbance. Consequently, ecological studies relying on modern observations or historical records may have difﬁculty assessing natural vegetation dynamics under current and future climate. We combined a sedimentary pollen record from Lago di Massacciucoli, Tuscany, Italy with simulations from the LANDCLIM dynamic vegetation model to determine what vegetation preceded intense human disturbance, how past changes in vegetation relate to ﬁre and browsing, and the potential of an extinct vegetation type under present climate. We simulated vegetation dynamics near Lago di Massaciucoli for the last 7,000 years using a local chironomid-inferred temperature reconstruction with combinations of three ﬁre regimes (small infrequent, large infrequent, small frequent) and three browsing intensities (no browsing, light browsing, and moderate browsing), and compared model output to pollen data. Simulations with low disturbance support polleninferred evidence for a mixed forest dominated by Quercus ilex (a Mediterranean species) and Abies alba (a montane species). Whereas pollen data record the collapse of A. alba after 6000 cal yr BP, simulated populations expanded with declining summer temperatures during the late Holocene. Simulations with increased ﬁre and browsing are consistent with evidence for expansion by deciduous species after A. alba collapsed. According to our combined paleoenvironmental and modeling evidence, mixed Q. ilex and A. alba forests remain possible with current climate and limited disturbance, and provide a viable management objective for ecosystems near the Mediterranean coast and in regions that are expected to experience a mediterranean-type climate in the future.
Keywords: Abies alba; Chironomids; Fire ecology; Holocene; Italy; Landscape model; mediterranean forest; Neolithic; pollen; Quercus ilex

Late postglacial paleoenvironmental change in the northeastern Mediterranean region: Combined palynological and molecular biomarker evidence - Kouli, K.; Gogou, A.; Bouloubassi, I.; Triantaphyllou, M. V.; Ioakim, Chr; Katsouras, G.; Roussakis, G.; Lykousis, V. (Quaternary International, 2012)
Three gravity cores collected from the NE Mediterranean (NEMR) across a transect from the northern Aegean Sea (North Skyros basin) to the south Cretan margin (SCM), were investigated for pollen and terrestrial biomarkers derived from epicuticular waxes of vascular plants during the last w20 ky. Pollen data show diversiﬁed mixed temperate forest in the northern borderlands and enhanced Mediterranean vegetation in the southern areas, documenting an NeS climatic trend. Terrestrial plant biomarkers and their diagnostic geochemical indices exhibit latitudinal patterns which are interpreted in terms of the different delivery pathways (ﬂuvial/runoff vs. atmospheric transport), resulting from the climate conditions during different periods. During the Late Glacial and early deglaciation periods (20e14 ka BP) relatively increased humidity (H-index) is recorded in the north Aegean Sea, while in the South drier climate was the limiting factor for vegetation development. During this interval, terrestrial n-alkanes showed increased accumulation rates, suggesting massive transport of terrestrial organic matter through runoffs and rivers, followed by weaker input after 14 ka BP. After w11 ka BP a major expansion of forest cover is evidenced in the NEMR, accompanied by a higher H-index because of the climatic amelioration. The forest vegetation exhibited regionally different characteristics, with cool temperate taxa being more abundant in the Aegean cores, while the SCM record is being featured by Mediterranean elements. At the onset of the Holocene and throughout the Holocene Climatic Optimum the delivery of terrestrial biomarkers increased and became more signiﬁcant in the Aegean sites compared to the SCM site. Within the Holocene, the average chain length (ACL) of long chain n-alkanes exhibits lower values in the northern Aegean than in the southeastern Aegean and SCM, indicating the predominance of warmer species southwards. Finally, the H-index records a conspicuous humidity increase between 5.4 and 4.3 ka BP in the south Aegean that coincides with an increase in the terrestrial biomarker supply and the deposition of a distinct sapropel-like layer, SMH (Sapropel Mid Holocene). Similar trends in T (temperature) and H indices are slightly delayed and attenuated in the northern Aegean and are accompanied by an increase in the ACL index. A noticeable increase in the accumulation rates (ARs) of terrestrial biomarkers and the HPA index values during this period are clearly recorded in all three cores, indicative of enhanced terrigenous inputs of organic matter along with higher in-situ preservation.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Aegean Sea; climatic variability (voyant); Holocene; Mediterranean; pollen; terrestrial biomarkers; Vegetation

Spatio-temporal patterns of Holocene environmental change in southern Sicily - Calò, Camilla; Henne, Paul D.; Curry, Brandon; Magny, Michel; Vescovi, Elisa; La Mantia, Tommaso; Pasta, Salvatore; Vannière, Boris; Tinner, Willy (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
Few examples of natural forest remain near the Mediterranean coast. Therefore, it is difﬁcult to study how coastal forests respond to climatic change or their resilience to human impact. We developed new sedimentary record of Holocene vegetation and ﬁre history at Lago Preola, a coastal lake in southwestern Sicily (Italy). In order to verify the existence of forest at large scale on the coast, we compare pollen from Lago Preola, a medium-sized lake (33 ha), to Gorgo Basso, a small lake (3 ha) located nearby with the aim of separating local from extra-local vegetation dynamics through time using pollen percentages and inﬂux. We then compare Lago Preola pollen to the record from Biviere di Gela, a large lagoon (120 ha) situated 160 km to the east in southern Sicily, to examine differences in vegetation dynamics between the two coastal areas during the Holocene. Lake-level reconstructions and ostracode analyses from Lago Preola provide vegetation-independent evidence of climate change, and help to disentangle human and climatic impacts on vegetation. Pollen data indicate Pistacia-dominated shrublands replaced open grasslands in the region surrounding Lago Preola by 9500 cal yr BP. This change coincided with rising lake levels and the development of an ostracode fauna typical of fresh waters. Evergreen forest dominated by Quercus ilex and Olea europaea started to expand by 7000 cal BP and consolidated at 6500 cal yr BP, when lake levels were near their Holocene high. Similarities between pollen from Lago Preola and Gorgo Basso demonstrate that forest was the dominant vegetation type in coastal Sicily during the middle Holocene at both regional and local scales, and even developed in the drier climatic setting around Biviere di Gela. Lake levels fell at Lago Preola after 7000 cal yr BP, with a strong decline accompanied by increasing salinity after 4500 cal yr BP. However, no transition in vegetation matched these inferred hydrological changes. Instead, forests persisted in the surrounding region until 2200 cal BP when human disturbance intensiﬁed. We propose that different climatic factors control lake levels and vegetation in coastal Mediterranean ecosystems. Whereas lake levels are most sensitive to the abundance of winter precipitation, coastal forests depend on spring precipitation and are limited by the length of summer drought. Moisture availability remained suitable for evergreen forests in coastal Sicily during the late Holocene, and humans, not a drier climate drove the regional forest decline.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: climate change; Holocene; Mediterranean; paleoecology; Paleohydrology; Sicily

The use of forest resources in central Iberia during the Late Iron Age. Insights from the wood charcoal analysis of Pintia, a Vaccaean oppidum - Rubiales, Juan M; Hernández, Laura; Romero, Fernando; Sanz, Carlos (Journal of Archaeological Science, 2011)
Charred woods may be used to effectively reconstruct past wood acquisition strategies. We used anthracological data from the pre-Roman settlement of Pintia (Padilla de Duero, Valladolid) to examine the use of forest resources at the local scale. Palaeoecological data revealed heterogeneous landscapes in the inland northern meseta with environments that offered diverse sources of wood for the inhabitants of Pintia, one of the ﬁrst cities of inland Iberia. Pines (Pinus pinea/pinaster and Pinus sylvestris/nigra) and both evergreen and deciduous Quercus L. and Juniperus L. were the main taxa identiﬁed as both fuelwood and construction elements, but the assemblages and frequencies of these taxa differed depending on their use. We also examined the potential of models from human ecology by considering the frequency, handling time and the relative technological value of each taxon to model how people gathered wood resources. The results suggest that although local availability affected the forest resources that were used by the Vaccaei people, speciﬁc taxa were positively selected for speciﬁc uses
Keywords: Anthracology; Holocene; Human behavioral ecology; Northern meseta; Palaeoethnobotany; Spain; Wood use

Expected trends and surprises in the Lateglacial and Holocene vegetation history of the Iberian Peninsula and Balearic Islands - Carrión, José S.; Fernández, Santiago; González-Sampériz, Penélope; Gil-Romera, Graciela; Badal, Ernestina; Carrión-Marco, Yolanda; López-Merino, Lourdes; López-Sáez, José a; Fierro, Elena; Burjachs, Francesc (Review of Palaeobotany and Palynology, 2010)
Recent, high-resolution palaeoecological records are changing the traditional picture of post-glacial vegetation succession in the Iberian Peninsula. In addition to the inﬂuence of Lateglacial and Early Holocene climatic changes, other factors are critical in the course of vegetation development and we observe strong regional differences. The ﬂoristic composition, location and structure of glacial tree populations and communities may have been primary causes of vegetation development. Refugial populations in the Baetic cordilleras would have been a source, but not the only one, for the early Lateglacial oak expansions. From Mid to Late Holocene, inertial, resilient, and rapid responses of vegetation to climatic change are described, and regional differences in the response are stressed. The role of ﬁre, pastoralism, agriculture, and other anthropogenic disturbances (such as mining), during the Copper, Bronze, Iberian, and Roman times, is analysed. The implications of ecological transitions in cultural changes, especially when they occur as societal collapses, are discussed.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Holocene; iberia; palaeobotany; palaeoecology; palaeogeography; quaternary

The historical origins of aridity and vegetation degradation in southeastern Spain - Carrión, J. S. S.; Fernández, S.; Jiménez-Moreno, G.; Fauquette, S.; Gil-Romera, G.; González-Sampériz, P.; Finlayson, C. (Journal of Arid Environments, 2010)
The complex relationships within modern landscapes cannot be understood without the beneﬁt of retrospective studies. We review palaeoenvironmental data for southeastern Spain, a landscape vulnerable to desertiﬁcation and with antiquity of human pressure on the landscape. A xerophytic component is discernible in the pollen diagrams of the southeastern peninsula ever since the Middle Miocene. During glacial stages of the Pleistocene, mountain grasslands and lowland steppes expanded, but tree vegetation, although episodically contracted, was ever present across the region, explaining part of the modern plant-species diversity. The magnitude of human impacts on vegetation during the Holocene has been highly variable, starting earlier (e.g. after c. 5000 cal years BP) in low-elevation areas and river basins. Forest degradation of the mountains started rather late during the Argaric period, and reached its maximum during the Roman occupation. Over the last millennia, natural and/or human-set ﬁres, combined with overgrazing, probably have pushed forests over a threshold leading to the spread of grassland, thorny scrub, junipers, and nitrophilous communities. The high degree of xerophytization observed today in southeastern Spain results from the long-term determinism of the Mid to Late Holocene climate aridiﬁcation, and the contingency of historical factors like ﬁre events and changes in prehistoric local economies involving resource exhaustion.
Keywords: historical biogeography; Holocene; palaeoecology; quaternary; Spain; Tertiary

Holocene circum-Mediterranean vegetation changes: Climate forcing and human impact - Jalut, Guy; Dedoubat, Jean Jacques; Fontugne, Michel; Otto, Thierry (Quaternary International, 2009)
The Mediterranean climate and its variability depend on global-scale climate patterns. Close correlations appear when comparing Holocene palaeoenvironmental data (lake levels, ﬂuvial activity, Mediterranean surface temperature and salinity, marine sedimentation) with the main stages of the history of the circum-Mediterranean vegetation. They indicate an evolution of the Mediterranean biome controlled by the climate and emphasize the teleconnections between the climate of the Mediterranean area and the global climatic system. In the circum-Mediterranean area, the Holocene can be divided into three periods: a lower humid Holocene (11 500–7000 cal BP) interrupted by dry episodes; a transition phase (7000–5500 cal BP) during which occurred a decrease in insolation as well as the installation of the present atmosphere circulation in the northern hemisphere; and an upper Holocene (5500 cal BP—present) characterized by an aridiﬁcation process. Throughout the Holocene, humans used and modiﬁed more or less strongly the environment but the climatic changes were the determining factors of the evolution of the Mediterranean biome. Societies had to adapt to natural environmental variations, their impact on the environment increasing the ecological consequences of the global changes.
Keywords: climate; climatic changes; Holocene; Mediterranean area; pollen data; vegetation dynamics (voyant)

Holocene circum-Mediterranean vegetation changes: Climate forcing and human impact - Jalut, Guy; Dedoubat, Jean Jacques; Fontugne, Michel; Otto, Thierry (Quaternary International, 2009)
The Mediterranean climate and its variability depend on global-scale climate patterns. Close correlations appear when comparing Holocene palaeoenvironmental data (lake levels, ﬂuvial activity, Mediterranean surface temperature and salinity, marine sedimentation) with the main stages of the history of the circum-Mediterranean vegetation. They indicate an evolution of the Mediterranean biome controlled by the climate and emphasize the teleconnections between the climate of the Mediterranean area and the global climatic system. In the circum-Mediterranean area, the Holocene can be divided into three periods: a lower humid Holocene (11 500–7000 cal BP) interrupted by dry episodes; a transition phase (7000–5500 cal BP) during which occurred a decrease in insolation as well as the installation of the present atmosphere circulation in the northern hemisphere; and an upper Holocene (5500 cal BP—present) characterized by an aridiﬁcation process. Throughout the Holocene, humans used and modiﬁed more or less strongly the environment but the climatic changes were the determining factors of the evolution of the Mediterranean biome. Societies had to adapt to natural environmental variations, their impact on the environment increasing the ecological consequences of the global changes.
Keywords: climate; climatic changes; Holocene; Mediterranean area; pollen data; vegetation dynamics (voyant)

Climate versus human-driven fire regimes in Mediterranean landscapes: the Holocene record of Lago dell’Accesa (Tuscany, Italy) - Vannière, B; Colombaroli, D; Chapron, E; Leroux, A; Tinner, W; Magny, M (Quaternary Science Reviews, 2008)
A high-resolution sedimentary charcoal record from Lago dell’Accesa in southern Tuscany reveals numerous changes in fire regime over the last 11.6kyr cal.BP and provides one of the longest gap-free series from Italy and the Mediterranean region. Charcoal analyses are coupled with gamma density measurements, organic-content analyses, and pollen counts to provide data about sedimentation and vegetation history. A comparison between fire frequency and lake-level reconstructions from the same site is used to address the centennial variability of fire regimes and its linkage to hydrological processes. Our data reveal strong relationships among climate, fire, vegetation, and land-use and attest to the paramount importance of fire in Mediterranean ecosystems. The mean fire interval (MFI) for the entire Holocene was estimated to be 150yr, with a minimum around 80yr and a maximum around 450yr. Between 11.6 and 3.6kyrcal.BP, up to eight high-frequency fire phases lasting 300–500yr generally occurred during shifts towards low lake-level stands (ca 11,300, 10,700, 9500, 8700, 7600, 6200, 5300, 3400, 1800 and 1350cal. yrBP). Therefore, we assume that most of these shifts were triggered by drier climatic conditions and especially a dry summer season that promoted ignition and biomass burning. At the beginning of the Holocene, high climate seasonality favoured fire expansion in this region, as inmany other ecosystems of the northern and southern hemispheres. Human impact affected fire regimes and especially fire frequencies since the Neolithic (ca 8000–4000cal.yrBP). Burning as a consequence of anthropogenic activities becamemore frequent after the onset of the Bronze Age (ca 3800–3600cal. yrBP) and appear to be synchronous with the development of settlements in the region, slash-and-burn agriculture, animal husbandry, and mineral exploitation. The anthropogenic phases with maximum fire activity corresponded to greater sensitivity of the vegetation and triggered significant changes in vegetational communities (e.g. temporal declines of Quercus ilex forests and expansion of shrublands and macchia). The link between fire and climate persisted during the mid- and late Holocene, when human impact on vegetation and the fire regime was high. This finding suggests that climatic conditions were important for fire occurrence even under strongly humanised ecosystem conditions.
Keywords: CHARCOAL ANALYSIS; Climatic conditions; Fire regime; Holocene; human activities; Pollen analysis; Vegetation history (voyant)

Climate versus human-driven fire regimes in Mediterranean landscapes: the Holocene record of Lago dell’Accesa (Tuscany, Italy) - Vannière, B.; Colombaroli, D.; Chapron, E.; Leroux, A.; Tinner, W.; Magny, M. (Quaternary Science Reviews, 2008)
A high-resolution sedimentary charcoal record from Lago dell’Accesa in southern Tuscany reveals numerous changes in fire regime over the last 11.6kyr cal.BP and provides one of the longest gap-free series from Italy and the Mediterranean region. Charcoal analyses are coupled with gamma density measurements, organic-content analyses, and pollen counts to provide data about sedimentation and vegetation history. A comparison between fire frequency and lake-level reconstructions from the same site is used to address the centennial variability of fire regimes and its linkage to hydrological processes. Our data reveal strong relationships among climate, fire, vegetation, and land-use and attest to the paramount importance of fire in Mediterranean ecosystems. The mean fire interval (MFI) for the entire Holocene was estimated to be 150yr, with a minimum around 80yr and a maximum around 450yr. Between 11.6 and 3.6kyrcal.BP, up to eight high-frequency fire phases lasting 300–500yr generally occurred during shifts towards low lake-level stands (ca 11,300, 10,700, 9500, 8700, 7600, 6200, 5300, 3400, 1800 and 1350cal. yrBP). Therefore, we assume that most of these shifts were triggered by drier climatic conditions and especially a dry summer season that promoted ignition and biomass burning. At the beginning of the Holocene, high climate seasonality favoured fire expansion in this region, as inmany other ecosystems of the northern and southern hemispheres. Human impact affected fire regimes and especially fire frequencies since the Neolithic (ca 8000–4000cal.yrBP). Burning as a consequence of anthropogenic activities becamemore frequent after the onset of the Bronze Age (ca 3800–3600cal. yrBP) and appear to be synchronous with the development of settlements in the region, slash-and-burn agriculture, animal husbandry, and mineral exploitation. The anthropogenic phases with maximum fire activity corresponded to greater sensitivity of the vegetation and triggered significant changes in vegetational communities (e.g. temporal declines of Quercus ilex forests and expansion of shrublands and macchia). The link between fire and climate persisted during the mid- and late Holocene, when human impact on vegetation and the fire regime was high. This finding suggests that climatic conditions were important for fire occurrence even under strongly humanised ecosystem conditions.
Keywords: CHARCOAL ANALYSIS; Climatic conditions; Fire regime; Holocene; human activities; Pollen analysis; Vegetation history (voyant)

Fire-vegetation interactions during the Mesolithic-Neolithic transition at Lago dell'Accesa, Tuscany, Italy - Colombaroli, Daniele; Vannière, Boris; Emmanuel, Chapron; Magny, Michel; Tinner, Willy (HOLOCENE, 2008)
A new core from the centre of Lago dell'Accesa (Tuscany, Italy) was sampled for pollen and charcoal analyses to provide a high-resolution sequence from 8400 to 7000 cal. yr BP. We combined series of microscopic charcoal, macroscopic charcoal and pollen to address the response of vegetation to fire at different spatial scales. Before 7900 cal. yr BP, broadleaved evergreen forests of Quercus ilex were the most important vegetational type in the area of Lago dell'Accesa. The subsequent decline of Q. ilex occurred when human-induced fires increased at the Mesolithic/Neolithic transition (c. 8000 cal. yr BP). Cross-correlation analyses show that fire was a key factor for vegetational change. Higher fire incidence affected the forest composition, converting evergreen forests to high-diversity open, partly deciduous forests and shrubby communities. The correlation is more pronounced at a local scale (macroscopic charcoal), whereas at a regional scale (microscopic charcoal) the vegetation followed the fire intervals with a more marked time lag (10-100 years). Climatic change, such as wetter periods inferred from lake levels, may have directly influenced the vegetational change, exacerbating the effect of human impact. Our study suggests that the disruption of evergreen broadleaved forests occurred when mean fire interval reached values as high as those of today's highly disturbed Mediterranean ecosystems. Hence broadleaved evergreen forests may not be as fire-resilient as assumed according to modern ecological paradigms. In view of the projected increase in fire frequency as a consequence of global warming, the present relict forests of Quercus ilex will be strongly affected.
Keywords: climate change; Fire ecology; Fire history; Holocene; Italy; macroscopic charcoal; Mediterranean vegetation; mesolithic; microscopic charcoal; Neolithic; Quercus ilex; tuscany

Fire-vegetation interactions during the Mesolithic-Neolithic transition at Lago dell'Accesa, Tuscany, Italy - Colombaroli, Daniele; Vannière, Boris; Emmanuel, Chapron; Magny, Michel; Tinner, Willy (HOLOCENE, 2008)
A new core from the centre of Lago dell'Accesa (Tuscany, Italy) was sampled for pollen and charcoal analyses to provide a high-resolution sequence from 8400 to 7000 cal. yr BP. We combined series of microscopic charcoal, macroscopic charcoal and pollen to address the response of vegetation to fire at different spatial scales. Before 7900 cal. yr BP, broadleaved evergreen forests of Quercus ilex were the most important vegetational type in the area of Lago dell'Accesa. The subsequent decline of Q. ilex occurred when human-induced fires increased at the Mesolithic/Neolithic transition (c. 8000 cal. yr BP). Cross-correlation analyses show that fire was a key factor for vegetational change. Higher fire incidence affected the forest composition, converting evergreen forests to high-diversity open, partly deciduous forests and shrubby communities. The correlation is more pronounced at a local scale (macroscopic charcoal), whereas at a regional scale (microscopic charcoal) the vegetation followed the fire intervals with a more marked time lag (10-100 years). Climatic change, such as wetter periods inferred from lake levels, may have directly influenced the vegetational change, exacerbating the effect of human impact. Our study suggests that the disruption of evergreen broadleaved forests occurred when mean fire interval reached values as high as those of today's highly disturbed Mediterranean ecosystems. Hence broadleaved evergreen forests may not be as fire-resilient as assumed according to modern ecological paradigms. In view of the projected increase in fire frequency as a consequence of global warming, the present relict forests of Quercus ilex will be strongly affected.
The following values have no corresponding Zotero field: pub-location: 1 OLIVERS YARD, 55 CITY ROAD, LONDON EC1Y 1SP, ENGLAND publisher: SAGE PUBLICATIONS LTD
Keywords: climate change; Fire ecology; Fire history; Holocene; Italy; macroscopic charcoal; Mediterranean vegetation; mesolithic; microscopic charcoal; Neolithic; Quercus ilex; tuscany

Holocene hydrological and vegetation changes in southern France inferred by the study of an alluvial travertine system (Saint-Guilhem-le-Désert, Hérault) - Ali, Adam Ahmed; Roiron, Paul; Chabal, Lucie; Ambert, Paul; Gasco, Jean; André, Joël; Terral, Jean-Frédéric (Comptes Rendus Geoscience, 2008)
A geobotanical study of the travertine system of Saint-Guilhem-le-Désert (southern France) was carried out in order to reconstruct the local Holocene environment in a region where the postglacial vegetation history is poorly documented. The travertinisation process has started at ca. 8500 cal. BP, in a landscape dominated by Pinus sylvestris type (probably Pinus nigra sub sp. salzmannii). Around 7000 cal. BP, the travertine system recorded torrential events not evidenced at the regional scale, showing the particularity of the Verdus hydrological regime. More recently, ca. 5100 cal. BP, a lake or a marsh was ﬁlled within the Verdus plain, as attested to by sand and silt particles accumulated in the sequence. The present-day vegetation dominated by Quercus ilex, on south facing slopes, was most likely established between the Bronze Age and the Gallo-Roman period correlatively to the decline of Pinus nigra and deciduous Quercus, most probably under human inﬂuence
Keywords: 14C; Charcoals; Holocene; Leaf imprints; Southern France; Travertine; Vegetation dynamics

Holocene hydrological and vegetation changes in southern France inferred by the study of an alluvial travertine system (Saint-Guilhem-le-Désert, Hérault) - Ali, Adam Ahmed; Roiron, Paul; Chabal, Lucie; Ambert, Paul; Gasco, Jean; André, Joël; Terral, Jean-Frédéric (Comptes Rendus Geoscience, 2008)
A geobotanical study of the travertine system of Saint-Guilhem-le-Désert (southern France) was carried out in order to reconstruct the local Holocene environment in a region where the postglacial vegetation history is poorly documented. The travertinisation process has started at ca. 8500 cal. BP, in a landscape dominated by Pinus sylvestris type (probably Pinus nigra sub sp. salzmannii). Around 7000 cal. BP, the travertine system recorded torrential events not evidenced at the regional scale, showing the particularity of the Verdus hydrological regime. More recently, ca. 5100 cal. BP, a lake or a marsh was ﬁlled within the Verdus plain, as attested to by sand and silt particles accumulated in the sequence. The present-day vegetation dominated by Quercus ilex, on south facing slopes, was most likely established between the Bronze Age and the Gallo-Roman period correlatively to the decline of Pinus nigra and deciduous Quercus, most probably under human inﬂuence
Keywords: 14C; Charcoals; Holocene; Leaf imprints; Southern France; Travertine; Vegetation dynamics

Orbital- and sub-orbital-scale climate impacts on vegetation of the western Mediterranean basin over the last 48,000 yr - Fletcher, William J; Sánchez Goñi, Maria Fernanda (Quaternary Research, 2008)
High-resolution pollen analysis of Alborán Sea core MD95-2043 provides a 48-ka continuous vegetation record that can be directly correlated with sea surface and deep-water changes. The reliability of this record is supported by comparison with that of Padul (Sierra Nevada, Spain). Marine Isotope Stage (MIS) 3 was characterised by ﬂuctuations in Quercus forest cover in response to Dansgaard-Oeschger climate variability. MIS 2 was characterised by the dominance of semi-desert vegetation. Despite overall dry and cold conditions during MIS 2, Heinrich events (HEs) 2 and 1 were distinguished from the last glacial maximum by more intensely arid conditions. Taxon-speciﬁc vegetation responses to a tripartite climatic structure within the HEs are observed. In MIS 1, the Bölling-Allerød was marked by rapid afforestation, while a re-expansion of semidesert environments occurred during the Younger Dryas. The maximum development of mixed Quercus forest occurred between 11.7 and 5.4 cal ka BP, with forest decline since 5.4 cal ka BP. On orbital timescales, a long-term expansion of semi-desert vegetation from MIS 3 into MIS 2 reﬂects global ice-volume trends, while Holocene arboreal decline reﬂects summer insolation decrease. The inﬂuence of precession on the amplitude of forest development and vegetation composition is also detected
Keywords: Dansgaard-Oeschger variability; Heinrich events; Holocene; Iberian margin; Land–sea correlation; LGM; Marine palynology; Mediterranean Region; Precession

Orbital- and sub-orbital-scale climate impacts on vegetation of the western Mediterranean basin over the last 48,000 yr - Fletcher, William J.; Sánchez Goñi, Maria Fernanda (Quaternary Research, 2008)
High-resolution pollen analysis of Alborán Sea core MD95-2043 provides a 48-ka continuous vegetation record that can be directly correlated with sea surface and deep-water changes. The reliability of this record is supported by comparison with that of Padul (Sierra Nevada, Spain). Marine Isotope Stage (MIS) 3 was characterised by ﬂuctuations in Quercus forest cover in response to Dansgaard-Oeschger climate variability. MIS 2 was characterised by the dominance of semi-desert vegetation. Despite overall dry and cold conditions during MIS 2, Heinrich events (HEs) 2 and 1 were distinguished from the last glacial maximum by more intensely arid conditions. Taxon-speciﬁc vegetation responses to a tripartite climatic structure within the HEs are observed. In MIS 1, the Bölling-Allerød was marked by rapid afforestation, while a re-expansion of semidesert environments occurred during the Younger Dryas. The maximum development of mixed Quercus forest occurred between 11.7 and 5.4 cal ka BP, with forest decline since 5.4 cal ka BP. On orbital timescales, a long-term expansion of semi-desert vegetation from MIS 3 into MIS 2 reﬂects global ice-volume trends, while Holocene arboreal decline reﬂects summer insolation decrease. The inﬂuence of precession on the amplitude of forest development and vegetation composition is also detected
The following values have no corresponding Zotero field: publisher: University of Washington
Keywords: Dansgaard-Oeschger variability; Heinrich events; Holocene; Iberian margin; Land–sea correlation; LGM; Marine palynology; Mediterranean Region; Precession

The 8.2ka event and Early–Mid Holocene forests, fires and flooding in the Central Ebro Desert, NE Spain - Davis, B; Stevenson, A (Quaternary Science Reviews, 2007)
The impact of the 8.2 ka cooling event during the Early–Mid Holocene has not been widely observed in Southern Europe, which in contrast to Northern Europe, was already experiencing a cooler than present climate at this time. Multi-proxy analysis of sediment cores from two closed-basin saline lakes in the Central Ebro Desert (NE Spain) has allowed us to investigate the impact of climatic changes around the time of this event in more detail. Long-term changes in climate between the Early and Mid Holocene indicate a shift in winter to a more positive NAO, resulting in declining lake levels in one lake sensitive to winter groundwater recharge, and cooler winter temperatures reconstructed from pollen–climate analysis. Reconstructed summer temperatures also declined over this period while annual precipitation and forest cover increased, interpreted as a result of enhanced convection-driven summer precipitation association with a northward displacement of the sub-tropical high pressure. Around 8.2 ka, a marked increase in ﬁre frequency is shown between ca 8.8 and 8.0 ka BP, along with an expansion of ﬁre-tolerant evergreen oak and peak in water levels in a second storm run-off fed lake. A maximum in ﬁre intensity occurred with the deposition of a charcoal layer at both lake sites dated to 81507130 and 82857135 cal BP, respectively. The increase in ﬁre is largely attributed to a temporary return southward of the summer sub-tropical high pressure over the Mediterranean, which not only increased summer aridity, but also caused a contradictory regional warming before Hemispheric cooling set in
Keywords: climate changes; Ebro basin; Fire frequency (voyant); Holocene; Mediterranean; water levels; winter/summer temperatures

The 8.2ka event and Early–Mid Holocene forests, fires and flooding in the Central Ebro Desert, NE Spain - Davis, B.; Stevenson, A. (Quaternary Science Reviews, 2007)
The impact of the 8.2 ka cooling event during the Early–Mid Holocene has not been widely observed in Southern Europe, which in contrast to Northern Europe, was already experiencing a cooler than present climate at this time. Multi-proxy analysis of sediment cores from two closed-basin saline lakes in the Central Ebro Desert (NE Spain) has allowed us to investigate the impact of climatic changes around the time of this event in more detail. Long-term changes in climate between the Early and Mid Holocene indicate a shift in winter to a more positive NAO, resulting in declining lake levels in one lake sensitive to winter groundwater recharge, and cooler winter temperatures reconstructed from pollen–climate analysis. Reconstructed summer temperatures also declined over this period while annual precipitation and forest cover increased, interpreted as a result of enhanced convection-driven summer precipitation association with a northward displacement of the sub-tropical high pressure. Around 8.2 ka, a marked increase in ﬁre frequency is shown between ca 8.8 and 8.0 ka BP, along with an expansion of ﬁre-tolerant evergreen oak and peak in water levels in a second storm run-off fed lake. A maximum in ﬁre intensity occurred with the deposition of a charcoal layer at both lake sites dated to 81507130 and 82857135 cal BP, respectively. The increase in ﬁre is largely attributed to a temporary return southward of the summer sub-tropical high pressure over the Mediterranean, which not only increased summer aridity, but also caused a contradictory regional warming before Hemispheric cooling set in
Keywords: climate changes; Ebro basin; Fire frequency (voyant); Holocene; Mediterranean; water levels; winter/summer temperatures

The Holocene and Upper Pleistocene pollen sequence of Carihuela Cave, southern Spain - Fernández, Santiago; Fuentes, Noemí; Carrión, José S.; González-Sampériz, Penélope; Montoya, Encarna; Gil, Graciela; Vega-Toscano, Gerardo; Riquelme, José a (Geobios, 2007)
A new pollen sequence (ca. 15,700–1250 yr BP) is presented for three stratigraphical sections of Carihuela Cave (Granada, southeastern Spain), thus completing a record that covers from the last Interglacial to late Holocene. The Late Glacial is characterized by open landscapes with junipers and early colonisation of Quercus, while the Holocene is depicted by mixed oak forests, with a diversity of broad-leaf trees and scrub, which decrease after ca. 5470 yr BP synchronously with the expansion of xerophytes and occurrence of indicators of anthropogenic disturbance. The whole pollen record of Carihuela ﬁts into the general trends described for reference pollen sites of southern Europe, including Padul in the province of Granada, and other sequences from Mediterranean Spain, through which the heterogeneity of environmental change increases from mid to late Holocene. We conclude that, in contrast with other regions of Spain, deciduous Quercus-dominated forests are very old in eastern Andalusia, thus conﬂicting with ﬂoristic phytosociological models of vegetation change that imply that monospeciﬁc Q. ilex/ rotundifolia woodlands are the potential mature forest in the region. Dating results suggest that the last Neanderthals of Carihuela lived between ca. 28,440 and 21,430 yr BP, which agrees with the postulation that southern Spain was the latest refugium for this human species in Europe
Keywords: historical biogeography; Holocene; palaeoecology; Spain; Upper Pleistocene; vegetation history

The Holocene and Upper Pleistocene pollen sequence of Carihuela Cave, southern Spain - Fernández, Santiago; Fuentes, Noemí; Carrión, José S.; González-Sampériz, Penélope; Montoya, Encarna; Gil, Graciela; Vega-Toscano, Gerardo; Riquelme, José a. (Geobios, 2007)
A new pollen sequence (ca. 15,700–1250 yr BP) is presented for three stratigraphical sections of Carihuela Cave (Granada, southeastern Spain), thus completing a record that covers from the last Interglacial to late Holocene. The Late Glacial is characterized by open landscapes with junipers and early colonisation of Quercus, while the Holocene is depicted by mixed oak forests, with a diversity of broad-leaf trees and scrub, which decrease after ca. 5470 yr BP synchronously with the expansion of xerophytes and occurrence of indicators of anthropogenic disturbance. The whole pollen record of Carihuela ﬁts into the general trends described for reference pollen sites of southern Europe, including Padul in the province of Granada, and other sequences from Mediterranean Spain, through which the heterogeneity of environmental change increases from mid to late Holocene. We conclude that, in contrast with other regions of Spain, deciduous Quercus-dominated forests are very old in eastern Andalusia, thus conﬂicting with ﬂoristic phytosociological models of vegetation change that imply that monospeciﬁc Q. ilex/ rotundifolia woodlands are the potential mature forest in the region. Dating results suggest that the last Neanderthals of Carihuela lived between ca. 28,440 and 21,430 yr BP, which agrees with the postulation that southern Spain was the latest refugium for this human species in Europe
Keywords: historical biogeography; Holocene; palaeoecology; Spain; Upper Pleistocene; vegetation history

Vegetation history, climate and human impact over the last 15,000 years at Lago dell’Accesa (Tuscany, Central Italy) - Drescher-Schneider, Ruth; de Beaulieu, Jacques-Louis; Magny, Michel; Walter-Simonnet, Anne-Véronique; Bossuet, Gilles; Millet, Laurent; Brugiapaglia, Elisabetta; Drescher, Anton (Vegetation History and Archaeobotany, 2007)
Interdisciplinary studies of the sediments of Lago dell’Accesa started in 2001. We present here results from the palynological study. The pollen diagram provides a record of vegetation and climatic change spanning over 15,000 years. The oldest pollen spectra show a late-glacial steppe vegetation typical of central and southern Italy during this period. The Late-glacial Interstadial, interrupted by two cooling events, is dominated by open deciduous oak forests. The Younger Dryas is represented by 150 cm of sediment and shows the presence of steppic vegetation. The Holocene vegetation is characterised by alternating dominance of deciduous oaks and Quercus ilex. The three zones characterised by Q. ilex are accompanied by peat layers marking lake-level lowering at ca. 8600–7900, 4600–4300 and 3700–2800 cal b.p. Between approximately 9000 and 6000 cal b.p. extensive Abies-forests existed on the Colline Metallifere located 15–20 km to the north and northeast of the lake. Local ﬁr populations may also have existed by the lake. Human impact starts at approximately 8000 cal b.p. during the Neolithic period, and increases at ca. 4300 cal b.p. Castanea and Juglans pollen is recorded from ca. 2800 cal b.p. The impact of the Etruscan settlement near the lakeshore is shown in the increasing values of arable crops, species of secondary forest canopy (Ericaceae, Pinus, Pistacia, Myrtus) and anthropogenic indicators (Chenopodiaceae, Plantago lanceolata, Rumex etc).
Keywords: Abies; Central Italy; Holocene; human impact; Late Pleistocene; Mediterranean vegetation; Pollen analysis

Large-Scale Post-Glacial Distribution of Vegetation Structures in the Mediterranean Region - Quézel, Pierre (Recent Dynamics of the Mediterranean Vegetation and Landscape, 2005)
This chapter contains sections titled: * Introduction * The Large-Scale Vegetation Structures * Conclusions * Acknowledgements
The following values have no corresponding Zotero field: periodical: Recent Dynamics of the Mediterranean Vegetation and Landscape electronic-resource-num: 10.1002/0470093714.ch1
Keywords: annual grasslands; broadleaved forests; circum-Mediterranean; Holocene; matorrals and steppes; Mediterranean flora; mediterranean grasslands; Mediterranean vegetation; post-glacial distribution; pre-steppe-forests (citation)

Large-Scale Post-Glacial Distribution of Vegetation Structures in the Mediterranean Region - Quézel, Pierre (Recent Dynamics of the Mediterranean Vegetation and Landscape, 2005)
This chapter contains sections titled: * Introduction * The Large-Scale Vegetation Structures * Conclusions * Acknowledgements
Keywords: annual grasslands; broadleaved forests; circum-Mediterranean; Holocene; matorrals and steppes; Mediterranean flora; mediterranean grasslands; Mediterranean vegetation; post-glacial distribution; pre-steppe-forests (citation)

Climatic changes since the Late-glacial/Holocene transition in La Mancha Plain (South-central Iberian Peninsula, Spain) and their incidence on Las Tablas de Daimiel - Dorado, Miriam; Rodr, Ana Valdeolmillos; Zapata, M. Blanca Ruiz; Jos, M.; Garc, Gil; Bustamante, Irene De (Quaternary International, 2002)
A palynological and lithological continuous record from La Mancha Plain (South-central Iberian Peninsula, Spain) is presented. The obtained results have permitted the reconstruction of the climatic evolution in the area since the Late-glacial/Holocene transition. The end of the Late-glacial was characterized by a cold and arid climate and it concluded at about 98907180 yr BP. In the Early Holocene a slight climatic amelioration began, being interrupted by a more arid phase around 8500 yr BP. The Holocene Climatic Optimum started from ca. 8000 yr BP and was characterized by higher temperatures and more humidity. During the MidHolocene–Late Holocene times a stage of marked aridity occurred towards 5000 yr BP that preceded the development of a dry mediterranean climate. Under this new climate a short-time arid phase took place around 2500 yr BP after which the mediterranean conditions became accentuated, with an increasing dry climate. This climatic evolution has affected the characteristics of the marshlands of Las Tablas de Daimiel National Park, originating changes in the sedimentary environment. This environment was mainly ﬂuvial until the end of the Holocene Climatic Optimum and became lacustrine–palustrine from the beginning of the more arid conditions.
Keywords: arid phase; Climatic conditions; Evergreen and deciduous species (voyant); Holocene; Pollen analysis; Quercus; Spain

Climatic changes since the Late-glacial/Holocene transition in La Mancha Plain (South-central Iberian Peninsula, Spain) and their incidence on Las Tablas de Daimiel - Dorado, Miriam; Rodr, Ana Valdeolmillos; Zapata, M Blanca Ruiz; Jos, M; Garc, Gil; Bustamante, Irene De (Quaternary International, 2002)
A palynological and lithological continuous record from La Mancha Plain (South-central Iberian Peninsula, Spain) is presented. The obtained results have permitted the reconstruction of the climatic evolution in the area since the Late-glacial/Holocene transition. The end of the Late-glacial was characterized by a cold and arid climate and it concluded at about 98907180 yr BP. In the Early Holocene a slight climatic amelioration began, being interrupted by a more arid phase around 8500 yr BP. The Holocene Climatic Optimum started from ca. 8000 yr BP and was characterized by higher temperatures and more humidity. During the MidHolocene–Late Holocene times a stage of marked aridity occurred towards 5000 yr BP that preceded the development of a dry mediterranean climate. Under this new climate a short-time arid phase took place around 2500 yr BP after which the mediterranean conditions became accentuated, with an increasing dry climate. This climatic evolution has affected the characteristics of the marshlands of Las Tablas de Daimiel National Park, originating changes in the sedimentary environment. This environment was mainly ﬂuvial until the end of the Holocene Climatic Optimum and became lacustrine–palustrine from the beginning of the more arid conditions.
Keywords: arid phase; Climatic conditions; Evergreen and deciduous species (voyant); Holocene; Pollen analysis; Quercus; Spain

Holocene pedoenvironmental situations in the eastern Sierra Morena region (Andújar, Spain) - Granados, N; Espejo, J M Recio (Quaternary International, 2002)
Analysis of soils and vegetational changes during the Holocene period in the eastern Sierra Morena region (Spain) indicates that Mediterranean soils with argillaceous horizons have replaced leptosols. Genesis of regosols has favoured development of mesophytic species
Keywords: Holocene; Sierra Morena (voyant); Soil; vegetation changes

Patterns and processes of Late Quaternary environmental change in a montane region of southwestern Europe - Carrión, J S (Quaternary Science Reviews, 2002)
This paper examines the Late Quaternary (c. 20,300–o505 cal yr BP) environmental history of Siles, a lake situated at 1320 m in the Segura mountains of southern Spain, with the goalof establishing the mechanisms exerting controlon vegetation change. Palaeoecological indicators include pollen, microcharcoal, spores of terrestrial plants, fungi, and non-siliceous algae, and other microfossils. The Siles sequence is shown to be sensitive to climatic change, although the control exerted by climate on vegetation is ultimately shaped by disturbances and species interactions, determining the occurrence of century-scale lags and threshold responses. Biotically induced changes of vegetation are also shown at the intrazonal level of variation. The new sequence is placed in the context of two previous records to postulate a picture of Holocene environmental change for the Segura region. The existence of mid-elevation glacial refugia for a number of temperate and Mediterranean trees is shown. A mid-Holocene phase (c. 7500– 5200 cal yr BP) emerges regionally as the time of maximum forest development and highest lake levels. The early Holocene occurs as a generally dry, pyrophytic period of pine forests, with grassland scrub in high altitudes, and the late Holocene as a period of protracted vegetation sensitivity, with return to development of pine forests, spread of xerophytic communities, and increased ﬁre activity, under the context of dry spells, localized anthropogenic disturbance, and shallowing and desiccation of lakes. Several events described here correlate with established times of abrupt transitions in the climates of northern Europe, the Mediterranean basin, north Africa, and the Sahel
Keywords: Holocene; Mediterranean (voyant); Pollen analysis; vegetation belts

Patterns and processes of Late Quaternary environmental change in a montane region of southwestern Europe - Carrión, J. S. (Quaternary Science Reviews, 2002)
This paper examines the Late Quaternary (c. 20,300–o505 cal yr BP) environmental history of Siles, a lake situated at 1320 m in the Segura mountains of southern Spain, with the goalof establishing the mechanisms exerting controlon vegetation change. Palaeoecological indicators include pollen, microcharcoal, spores of terrestrial plants, fungi, and non-siliceous algae, and other microfossils. The Siles sequence is shown to be sensitive to climatic change, although the control exerted by climate on vegetation is ultimately shaped by disturbances and species interactions, determining the occurrence of century-scale lags and threshold responses. Biotically induced changes of vegetation are also shown at the intrazonal level of variation. The new sequence is placed in the context of two previous records to postulate a picture of Holocene environmental change for the Segura region. The existence of mid-elevation glacial refugia for a number of temperate and Mediterranean trees is shown. A mid-Holocene phase (c. 7500– 5200 cal yr BP) emerges regionally as the time of maximum forest development and highest lake levels. The early Holocene occurs as a generally dry, pyrophytic period of pine forests, with grassland scrub in high altitudes, and the late Holocene as a period of protracted vegetation sensitivity, with return to development of pine forests, spread of xerophytic communities, and increased ﬁre activity, under the context of dry spells, localized anthropogenic disturbance, and shallowing and desiccation of lakes. Several events described here correlate with established times of abrupt transitions in the climates of northern Europe, the Mediterranean basin, north Africa, and the Sahel
Keywords: Holocene; Mediterranean (voyant); Pollen analysis; vegetation belts

Fine-resolution Upper Weichselian and Holocene palynological record from Navarrés (Valencia, Spain) and a discussion about factors of Mediterranean forest succession - Carrión, J. S.; Geel, B. Van (Review of Palaeobotany and Palynology, 1999)
A detailed study is presented of the Upper Pleistocene and Holocene pollen sequence of the Navarre´s peat deposit (Valencia, eastern Spain) including non-pollen palynomorphs, Characeae gyrogonites, seeds and charcoal abundance. The study covers the period from ca. 30,900 to 3160 yr B.P. The last glacial vegetation is characterised by Pinus–Artemisia– Ephedra assemblages. This dominance is interrupted between ca. 30,260 and 27,890 yr B.P. by the development of Quercus, Pinus pinaster, deciduous trees and Mediterranean shrubs, suggesting the proximity of glacial refugia and an expansion of their vegetation under inﬂuence of a milder climate. A Younger Dryas signal is noticed by increases of Artemisia and Ephedra around 10,380 yr B.P. There is no immediate response of Quercus to the Late Glacial and Holocene climatic ameliorations and Pinus continues to dominate the landscape until removed at ca. 5930 yr B.P., presumably by severe ﬁre events whose causes are discussed in the light of palynological, anthracological and paleoclimatical data
Keywords: Holocene; navarrés; paleoecology; pollen; quaternary; Spain; vegetation history; younger dryas

Fine-resolution Upper Weichselian and Holocene palynological record from Navarrés (Valencia, Spain) and a discussion about factors of Mediterranean forest succession - Carrión, J S; Geel, B Van (Review of Palaeobotany and Palynology, 1999)
A detailed study is presented of the Upper Pleistocene and Holocene pollen sequence of the Navarre´s peat deposit (Valencia, eastern Spain) including non-pollen palynomorphs, Characeae gyrogonites, seeds and charcoal abundance. The study covers the period from ca. 30,900 to 3160 yr B.P. The last glacial vegetation is characterised by Pinus–Artemisia– Ephedra assemblages. This dominance is interrupted between ca. 30,260 and 27,890 yr B.P. by the development of Quercus, Pinus pinaster, deciduous trees and Mediterranean shrubs, suggesting the proximity of glacial refugia and an expansion of their vegetation under inﬂuence of a milder climate. A Younger Dryas signal is noticed by increases of Artemisia and Ephedra around 10,380 yr B.P. There is no immediate response of Quercus to the Late Glacial and Holocene climatic ameliorations and Pinus continues to dominate the landscape until removed at ca. 5930 yr B.P., presumably by severe ﬁre events whose causes are discussed in the light of palynological, anthracological and paleoclimatical data
Keywords: Holocene; navarrés; paleoecology; pollen; quaternary; Spain; vegetation history; younger dryas

The Holocene at Lac de Creno, Corsica, France: a key site for the whole island - REILLE, M; Gamisans, J; Andrieu-Ponel, V; De Beaulieu, J.-L. (New Phytologist, 1999)
Two Holocene lake sequences from Lac de Creno, Corsica were analysed on the basis of 119 pollen spectra and with the support of 13 14C-calibrated dates. The lower part of one of these sequences, corresponding to the late- glacial period, has been published previously. The first third of the Post-glacial is characterized by very particular forest dynamics, namely the absence of a role for deciduous Quercus and Corylus, the presence of mesophilous vegetation types dominated by Taxus, and the major forest role of Erica arborea at lower and mean altitude. At about 7440 cal BP, the occurrence of a major anthropogenic action brought about significant changes in the vegetation, notably an increase of deciduous Quercus and the expansion of Quercus ilex. Later, three major human-induced events are identified: the first, at about 2290 cal BP, is the cause of a short local expansion of Abies; the second, at about 1150 cal BP, is the degradation of deciduous forests to the benefit of Fagus; the third, at about 310 cal BP, corresponds to the disappearance of Fagus and its replacement by Pinus. Pollen data indicate that Q. ilex, Abies and Fagus are not indigenous in Corsica but spread there during the Postglacial ; this probably took place at about 6980 cal BP for Q. ilex.
Keywords: Corsica; glacial vegetation; Holocene; pollen spectra; vegetation history

Late Pleistocene and Holocene pollen stratigraphy at Lago di Vico, central Italy - Magri, Donatella; Sadori, Laura (Vegetation history and archaeobotany, 1999)
A new pollen record from Lago di Vico (core V1) provides fundamental new information towards re- construction of flora and vegetation history in central Italy during the last 90 000 years. The chronological framework is secured by seventeen AMS 14C dates, one 4°Ar/39Ar date and tephra analyses. At the base of the pol- len record, i.e. shortly after the 4°Ar/39Ar date 87 000+ 7000 B.P., three phases with significant expansion of trees are recorded in close succession. These forest phases, which stratigraphically correspond to St Ger- main II (and Ognon?) and precede pleniglacial steppe vegetation, are designated by the local names Etruria I, Etruria II and Etruria III. During the pleniglacial, a number of fluctuations of angiosperm mesophilous trees suggest the presence of tree refugia in the area. The low- est pollen concentration values are recorded at ca. 22 000 B.P. which corresponds with other pollen records from the region. The late-glacial is characterized by an expansion in the arboreal pollen curves that is less pro- nounced, however, than in other pollen profiles from Italy. The Holocene part of the profile is consistently dominated by deciduous oak pollen. No major changes in arboreal pollen composition are recorded but several marked and sudden declines of the tree pollen concentra- tion suggest that the forest cover underwent dramatic changes. Clear evidence for human impact is recorded only when cultivated crops became important which dates to ca. 26304-95 B.P.
Keywords: Central Italy; Crater lake; Holocene; Late Pleistocene; Pollen analysis

Holocene climatic change in Morocco: a quantitative reconstruction from pollen data - Cheddadi, R; Lamb, H F; Guiot, J; van der Kaars, S (Climate Dynamics, 1998)
Annual precipitation, July and January tem- peratures were reconstructed from a continuous Holo- cene pollen sequence from the Middle Atlas, Morocco, using the best modern analogues method. The recon- structions show a clear difference between the early and late Holocene: from &10 ka to &6.5 ka the climate was drier and warmer than during the period since 6.5 ka. The average value of annual precipitation was &870mm until 6.5 ka, then rose to &940 mm. Be- tween 10 ka and 6.5 ka January and July temperatures were about 4 °C higher than the present. Both temper- atures show a marked decrease between 7 ka and 6 ka. After 6.5 ka July and January temperatures fluctuated between 21 and 23 °C, and 2.5 and 5 °C respectively. January temperatures show a period of intermediate values (&3.5 °C) between 4 ka and 5.5 ka. The recon- structed climate values generally match palaeolim- nological data from the same core, which show five intervals of low lake level during the Holocene. They are also consistent with regional-scale COHMAP simulated palaeoclimate that shows contrasting pat- terns of rainfall variation between the northwester- nmost part of Africa and the intertropical band
APS
Keywords: climate; Holocene; Morocco; paleoclimate; pollen

Holocene climatic change in Morocco: a quantitative reconstruction from pollen data - Cheddadi, R.; Lamb, H. F.; Guiot, J.; van der Kaars, S. (Climate Dynamics, 1998)
Annual precipitation, July and January tem- peratures were reconstructed from a continuous Holo- cene pollen sequence from the Middle Atlas, Morocco, using the best modern analogues method. The recon- structions show a clear difference between the early and late Holocene: from &10 ka to &6.5 ka the climate was drier and warmer than during the period since 6.5 ka. The average value of annual precipitation was &870mm until 6.5 ka, then rose to &940 mm. Be- tween 10 ka and 6.5 ka January and July temperatures were about 4 °C higher than the present. Both temper- atures show a marked decrease between 7 ka and 6 ka. After 6.5 ka July and January temperatures fluctuated between 21 and 23 °C, and 2.5 and 5 °C respectively. January temperatures show a period of intermediate values (&3.5 °C) between 4 ka and 5.5 ka. The recon- structed climate values generally match palaeolim- nological data from the same core, which show five intervals of low lake level during the Holocene. They are also consistent with regional-scale COHMAP simulated palaeoclimate that shows contrasting pat- terns of rainfall variation between the northwester- nmost part of Africa and the intertropical band
APSAPS
Keywords: climate; Holocene; Morocco; paleoclimate; pollen

Reconstruction of Late-glacial and Holocene environments in southeast France based on the study of a 66-m long core from Biot, Alpes Maritimes - Nicol-Pichard, S; Dubar, M (VEGETATION HISTORY AND ARCHAEOBOTANY, 1998)
A pollen analytical study of a 66-m long core from the Prague valley, Plot, Alpes-Maritimes, France, suggests that thalwegs in eastern Provence may have served as refugia for mesophilous trees such as Tilia, Fagus and Abies during the last glacial period. During the Younger Dryas the vegetation was considerably less steppic in character than that described from western Provence. The varying role of taxa such as Quercus ilex-type in pollen profiles from the wider region suggests a longitudinal gradient in both climate and vegetation development in the French/Italian north-western mediterranean region during the Holocene.
Keywords: France Glacial refugia; Holocene; Late-glacial; Mediterranean; Pollen analysis

Sclerophyllous vegetation dynamics in the north of the Iberian peninsula during the last 16,000 years - RAMIL-REGO, P; RODRÍGUEZ-GUITIÁN, M; MUÑOZ-SOBRINO, C (Global Ecology and Biogeography, 1998)
We used pollen analysis to evaluate the dynamics of sclerophyllous arboreal taxa during the last 16,000 years. Quercus ilex type pollen and, to a lesser degree, other sclerophyllous elements (e.g. Olea and Phillyrea) have been documented during the Late-glacial in the majority of the sequences obtained in continental territories in the north of the Iberian peninsula, as well as in the eastern coastal/sub-coastal area in the Cantabric region. During the Late-glacial and the Holocene, sclerophyllous elements became widespread in many areas of the north Iberian peninsula (the Sil, Duero and Ebro depressions and the southernmost slopes of adjacent mountains), with the smallest pollinic representation of these taxa being for the most septentrional areas (coastal/sub-coastal territories and the northermost slopes of the Cantabrian-Atlantic Mountains). During these periods, there is no indication of the presence of Quercus ilex pollen in the northwestern territories, which would explain the absence of this species in the present-day landscape. Despite the widespread distribution that sclerophyllous elements have maintained during the last 16,000 years, they have never attained a predominant role in the landscape, having a smaller representation, both during hotter and colder phases, than deciduous forests, pine forests and mixed forests.
Keywords: Holocene; iberian peninsula; Late-glacial; palynology; Quercus ilex; sclerophyllous forests; species range; vegetation history

Late glacial and Holocene vegetation of the Corbières based on charcoal analysis at the Cova de l'espérit (Salses, Pyrénées orientales, France) - Solari, Maria-Eugenia; Vernet, Jean-Louis (Review of Palaeobotany and Palynology, 1992)
Charcoal analysis from the end of the Würm Glaciation and the Holocene at Cova de l'Espérit reveals the coexistence, in the Corbières region, of thermo-and meso-Mediterranean taxa. Three principal paleoecological phases are described: the first corresponds to the Upper Paleolithic (Würm III), the period of maximum cold, dominated by Juniperus assemblages. The second phase includes levels from the end of the Mesolithic and early Neolithic. It shows the appearance of mesothermic species such as Buxus sempervirens, Acer sp. and Quercus ilex, at the same time as the development of a thermophilic suite of species e.g. Olea europaea, Rosmarinus officinalis and Pistacia. During this period, the effect of man on the environment remained slight. The third phase consists of the middle Neolithic and more recent periods and reveals the degradation of the environment due to the development of agriculture and animal husbandry. The Garrigue—a mediterranean open human-influenced vegetation—has persisted up to the present.
Keywords: CHARCOAL ANALYSIS; Cova de l'Espérit; Holocene; human influence; vegetation history (PG)

The holocene- and upper pleistocene pollen record from Padul (Granada, Spain): A new study - Pons, A; REILLE, M (Palaeogeography, Palaeoclimatology, Palaeoecology, 1988)
Two borings were made at the site of Padul (Granada). Pollen analysis of 200 spectra from two successive sequences, 14.8 and 8 m deep, enables a description of the vegetational and climatic history of this region, the most southern one in Europe, from Early Würmian times. The chronology is supported by twenty-one 14C dates. Original equivalents are found for the great European Prewürm interstadials. A markedly arid though thermically not extreme episode, exactly equivalent to stage 4 of the marine isotopic stratigraphy, closes this relatively temperate period. The middle part of the Last Glacial shows climatic fluctuations that are poorly characterized, as is often the case in Europe for this period. A long section, very probably corresponding to the complete Last Pleniglacial, does not show any climatic amelioration. Towards 15,000 yr B.P. a change in the diagram is noted that can only be interpreted as reflecting a larger expansion of a regional steppe cover. This event, also reported on three occasions in southeast France, marks the beginning of the Oldest Dryas. The climatic amelioration of ca. 13,000 yr B.P. is far more pronounced here than anywhere else in Europe, whereas that at 10,000 yr B.P. is not so clearly marked. This unexpected result may be accounted for by the fact that Padul is the first continental site so far south and so near Pleniglacial refuges to be known: on the other hand, this result is consistent with what is known from oceanic isotopic stratigraphy. A quite new late-glacial and Holocene vegetational history is revealed, characterized by the early appearance and dominance of Quercus ilex oak forests of a southern type and the early occurrence of Quercus suber and Olea: it is the first account of a complete history of the postglacial reafforestation in a region with a modern semi-arid mediterranean climate. From the palaeoclimatic point of view, it shows that the hot and humid Holocene optimum was attained slightly before 8000 yr B.P. and that the Holocene climatic fluctuations were of but small amplitude.
Keywords: climatic fluctuations; Holocene; Padul; Pollen analysis; vegetation history (PG)